2020
DOI: 10.1002/jcp.30233
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Immunomodulatory effects of nanocurcumin on Th17 cell responses in mild and severe COVID‐19 patients

Abstract: In novel coronavirus disease 2019 (COVID‐19), the increased frequency and overactivation of T helper (Th) 17 cells and subsequent production of large amounts of proinflammatory cytokines result in hyperinflammation and disease progression. The current study aimed to investigate the therapeutic effects of nanocurcumin on the frequency and responses of Th17 cells in mild and severe COVID‐19 patients. In this study, 40 severe COVID‐19 intensive care unit‐admitted patients and 40 patients in mild condition were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 50 publications
3
120
0
Order By: Relevance
“…Clinical studies have demonstrated the effects of nanoencapsulated curcumin in patients with COVID-19. In the aforementioned study, a significant reduction in clinical manifestations of COVID-19 (fever, cough, and dyspnea) was observed in the group treated with nanocurcumin (patients with mild and severe disease) (Tahmasebi et al, 2020;Valizadeh et al, 2020). In addition, nanocurcumin reduced the mortality rate of these patients.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Clinical studies have demonstrated the effects of nanoencapsulated curcumin in patients with COVID-19. In the aforementioned study, a significant reduction in clinical manifestations of COVID-19 (fever, cough, and dyspnea) was observed in the group treated with nanocurcumin (patients with mild and severe disease) (Tahmasebi et al, 2020;Valizadeh et al, 2020). In addition, nanocurcumin reduced the mortality rate of these patients.…”
Section: Introductionmentioning
confidence: 80%
“…Patients with COVID-19 showed high mRNA expression and secretion of cytokines, IL-1β, IL-6, TNF-α, and IL-18, but showed a significant reduction in IL-6 and IL-1β after treatment with nanocurcumin (Valizadeh et al, 2020). Subsequently, exploring the modulatory mechanisms of nanocurcumin, the researchers demonstrated that the number of Th17 cells, gene expression, and serum Th17-mediated factors level (IL-17, IL-21, IL-23, and GM-CSF) were significantly reduced in both stages of the disease in the group of patients with COVID-19 treated with nanocurcumin (Tahmasebi et al, 2020).…”
Section: Effects Of Curcumin In the Covid-19-induced Inflammatory Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined application of vitamin C, curcumin and glycyrrhizic acid was found effective against this virus by regulation of crucial pathways (Kandeel & Al-Nazawi 2020). Clinical studies using nanoencapsulated curcumin significantly reduced symptoms of COVID-19 (fever, cough, and dyspnea) (Tahmasebi et al 2020;Valizadeh et al 2020).…”
Section: Eapenmentioning
confidence: 97%